Investor Protection and Legal Enforcement: Defaults and Digital-Age Illegal Investments - Edi Krisharyanto; Fries Melia Salviana (APPTHI, 2025)
This paper examines the current landscape of investor protection and legal enforcement in Indonesia, focusing on the rising prevalence of default cases and illegal investment schemes. As the Indonesian capital market expands, retail investors remain vulnerable to fraudulent financial products and contractual breaches. Using normative legal analysis combined with case studies of recent high-profile defaults, this research evaluates the effectiveness of the Financial Services Authority (OJK) and the existing regulatory framework in providing legal certainty. The findings suggest that although Indonesia has established comprehensive regulations, enforcement mechanisms remain inconsistent. Bureaucratic complexities and the absence of integrated digital monitoring often weaken implementation. The study also highlights challenges in asset recovery for victims of illegal investments, where legal proceedings frequently fail to restore financial losses. Strengthening investor protection requires more rigorous supervision, swifter judicial action, and greater public financial literacy to mitigate the impact of “shadow banking” and unauthorized investment entities.